The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20944/preprints201709.0061.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitory Properties of Neomycin Thin Film Formed on Carbon Steel in Sulfuric Acid Solution. Electrochemical and AFM Investigation

Abstract: Our study aims to implement a strategy to reduce the carbon steel corrosion rate in sulfuric acid solution, using an expired drug with adsorption affinity on the metal surface. To investigate the corrosion protection efficiency of an environmental friendly inhibitor, namely neomycin sulfate (NMS), the electrochemical measurements were applied on carbon steel immersed in 1.0 M H2SO4 solution with and without NMS. The protective layer formed on the steel surface was studied by atomic force microscopy (AFM). The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The inhibition efficiency (IE) was determined using eqs. and , this being presented in Table . IE=icorroicorricorrnormalo×100 IE=RpRpoRp×100 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition efficiency (IE) was determined using eqs. and , this being presented in Table . IE=icorroicorricorrnormalo×100 IE=RpRpoRp×100 …”
Section: Resultsmentioning
confidence: 99%
“…Organic compounds can adhere to metals, acting by physical or chemical adsorption on substrates through oxygen, nitrogen or sulfur atoms from their molecules, leading to the formation of coherent organized thin films and evenly distributed over the surfaces . Certain ligands form stable complexes with metal cations which can be adsorbed on the surface, enhancing the adherence, stability, and organized structure of the films …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous our studies we reported the results of our research on the electrochemical stability of some drugs, and of some dyes, as follows: metronidazole, benzocaine, hematoxylin, Brilliant Blue, Methylene blue, Methyl blue, Methylorange .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the samples (1 inch × 1 inch) were placed in a shaking incubator for the whole experimental period (24 h). To determine the amount of drug released, a 3 mL solution was taken from the outside released medium, and absorbance was measured at the selected λ max (lidocaine = 263 nm; neomycin = 262 nm) using UV–visible light spectroscopy and a standard curve; the amount of drug released was then calculated [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%